Assessment of Atmospheric Radiation Effects on Aircraft Safety Analysis - Gurdamar, Aycin; Engin, Seref Naci (IEEE, 2023)
This paper discusses the importance of safety engineering in the identification, mitigation, and elimination of hazards to achieve an acceptable level of risk for a product or system throughout its life cycle. Safety analysis is essential to airworthiness regulations and is required for the certification of a product, ensuring compliance with the related type certificate release and hence safety requirements. It involves evaluating functional hazard scenarios for each system function and classifying them in terms of severity. It focuses on the occurrence frequency of critical systematic and random failure conditions. This is achieved through fault tree analysis of combinations of failure conditions. The paper presents a generic study on atmospheric radiation effects on aircraft and methods for analytical calculation of system reliability characteristics using qualitative and quantitative analyses on susceptible parts and qualitative analysis at system and aircraft levels. The outcome of the study is the achievement of a sufficient confidence level of see for aircraft altitudes up to 35000ft with both calculation and observation results. Avionics operating at altitudes between 35000-60,000 feet constitute a risk factor and should be analysed case by case.
Keywords: single event effects; safety; avionics; aircraft; probability; safety assessment; reliability; Engineering; Remote Sensing